2012
DOI: 10.1128/jvi.00533-12
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS5A Disrupts STAT1 Phosphorylation and Suppresses Type I Interferon Signaling

Abstract: Responses to alpha interferon (IFN-␣)-based treatment are dependent on both host and viral factors and vary markedly among patients infected with different hepatitis C virus (HCV) genotypes (GTs).Patients infected with GT3 viruses consistently respond better to IFN treatment than do patients infected with GT1 viruses. The mechanisms underlying this difference are not well understood. In this study, we sought to determine the effects of HCV NS5A proteins from different genotypes on IFN signaling. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 51 publications
2
61
0
1
Order By: Relevance
“…For example, HCV NS3-NS4A blocks RIG-I signaling and cleaves MAVS protein to attenuate innate immunity (35). Our previous studies have demonstrated that HCV infection, HCV core protein, or NS5A protein expression selectively decrease phospho-STAT1 (P-STAT1) accumulation to block the type I IFN pathway response (7,8,9). In this study, we found that HCV evaded the restriction of EFTUD2 by downregulating its expression, providing another mechanism for HCV immune evasion.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For example, HCV NS3-NS4A blocks RIG-I signaling and cleaves MAVS protein to attenuate innate immunity (35). Our previous studies have demonstrated that HCV infection, HCV core protein, or NS5A protein expression selectively decrease phospho-STAT1 (P-STAT1) accumulation to block the type I IFN pathway response (7,8,9). In this study, we found that HCV evaded the restriction of EFTUD2 by downregulating its expression, providing another mechanism for HCV immune evasion.…”
Section: Discussionmentioning
confidence: 70%
“…Pathogen recognition triggers downstream signaling to activate transcription factors, such as interferon (IFN) regulatory factors (IRFs), to induce type I interferon secretion and stimulation of the JAK-STAT signaling pathway, leading to the expression of IFN-stimulated genes (ISGs), which presumptively mediate control of viral replica-tion (6). Our previous studies have demonstrated that signal transducer and activator of transcription 1 (STAT1) is the critical signaling component in innate antiviral immunity to HCV and that HCV core protein and nonstructural protein 5A (NS5A) are associated with decreased STAT1 levels (7)(8)(9). However, the precise mechanisms for HCV persistence are still incompletely understood.…”
mentioning
confidence: 99%
“…But in our study, the population at the 12-week treatment in the region ISDR became more similar to the HCV-JFH1 (Figure 3), an IFN sensitive strain. Chimeric subgenomic JFH1 replicon activity before and after IFN treatment HCV resistance to IFN has been attributed, in part, to the function of the NS5A protein (13)(14)(15)(16). To investigate how these NS5A changes on the influence of the virus replication and response to IFN, we constructed subgenomic JFH1 (wild type) and chimeric replicons (Figure 4).…”
Section: Evolution Of Hcv Rna After Standard Therapymentioning
confidence: 99%
“…Whether these therapies directly alleviate HCV-induced host oxidative stress, chronic inflammation, and altered lipid metabolism is still unintelligible. Activating or blocking molecular pathways [i.e., IFN/Janus kinase/ signal transducer and activator of transcription (STAT) (Datta et al, 2011;Kumthip et al, 2012;Miyaaki et al, 2008), Ras/Raf kinase/mitogen-activated protein kinases (MAPK) (Zhang et al, 2012), and peroxisome proliferator-activated receptor (PPAR)-related signal pathways (Agriesti et al, 2012)] may be additive therapeutic targets to IFN-a to further treat CHC patients who otherwise produce an IFN-a resistance.…”
Section: Introductionmentioning
confidence: 99%